Differences in soccer players' dynamic balance across levels of competition - Butler, R. J.; Southers, C.; Gorman, P. P.; Kiesel, K. B.; Plisky, P. J. (Journal of Athletic Training, 2012)
Context: Balance ability has been associated with performance and injury prevention in athletes. Few published reports have investigated the differences in dynamic balance abilities among male high school, collegiate, and professional soccer players. Objective: To examine the differences on the Lower Quarter Y-Balance Test in male high school, collegiate, and professional soccer players. Design: Descriptive laboratory study. Setting: Field testing. Patients or Other Participants: Dynamic balance data were collected for male high school (HS; n = 38), collegiate (n = 37), and professional (n = 44) soccer players during preparticipation physical examinations using the Lower Quarter Y Balance Test standardized protocol. Main Outcome Measure(s): For the Lower Quarter Y Balance Test, the participant reaches with 1 foot in the anterior, posteromedial, and posterolateral directions while standing on a centralized stance platform with the other foot. The test is performed for both left and right limbs. Differences in reach distances between competition levels were analyzed using a 1-way analysis of variance with significance set at P < .05. The HS group had a greater anterior reach distance than the other 2 groups. In contrast, the HS group had less reach distance in the posteromedial and posterolateral directions than the other groups. Also, HS players tended to exhibit a lower composite reach score than the other groups, but this difference was not significant (P = .08). No differences were observed among groups for bilateral symmetry in any of the reach directions. Conclusions: Dynamic balance performance varied with competition level. This may indicate that athletes' movement strategies may be different depending on the competition level and that normative values may need to be established for each competition level.